Le Petit Poucet digital ethnographié - Frank Cochoy (Revue d'anthropologie des connaissances)
In our digitalized world, “following the actors”, the historic motto of ANTinspired ethnography (Latour 2005), now means following the actors and their traces, and, through these traces, following their devices, avatars, identities and duplicated practices (Boullier 2017; Pantzar and Lammi 2017). Contemporary actors are like the fairytale character Little Thumb: they can disappear or become unobservable, and leave digital traces in the market forest that function like Little Thumb’s white pebbles and breadcrumbs, insofar as they can be followed to find information on actors’ practices and identities. In the press market examined in this article, we will meet a crowd of independent and adult Little Thumbs, who read France Vision, a major French weekly magazine, and watch (or do not watch) videos accessible through the QR codes printed on its pages. Based on the collection of digital traces recorded nationally over a ten-month period (June 2013–March 2014), the article presents a set of results showing what can be learned from a renewed ethnography of QR code traces.